Assessing the severity of Type 2 diabetes using clinical data‐based measures: a systematic review. Issue 6 (16th February 2019) - Zghebi, S. S.; Panagioti, M.; Rutter, M. K.; Ashcroft, D. M.; van Marwijk, H.; Salisbury, C.; Chew‐Graham, C. A.; Buchan, I.; Qureshi, N.; Peek, N.; Mallen, C.; Mamas, M.; et al.
Abstract: Aims: To identify and critically appraise measures that use clinical data to grade the severity of Type 2 diabetes. Methods: We searched MEDLINE, Embase and PubMed between inception and June 2018. Studies reporting on clinical data‐based diabetes‐specific severity measures in adults with Type 2 diabetes were included. We excluded studies conducted solely in participants with other types of diabetes. After independent screening, the characteristics of the eligible measures including design and severity domains, the clinical utility of developed measures, and the relationship between severity levels and health‐related outcomes were assessed. Results: We identified 6798 studies, of which 17 studies reporting 18 different severity measures (32 314 participants in 17 countries) were included: a diabetes severity index (eight studies, 44%); severity categories (seven studies, 39%); complication count (two studies, 11%); and a severity checklist (one study, 6%). Nearly 89% of the measures included diabetes‐related complications and/or glycaemic control indicators. Two of the severity measures were validated in a separate study population. More severe diabetes was associated with increased healthcare costs, poorer cognitive function and significantly greater risks of hospitalization and mortality. The identified measures differed greatly in terms of the included domains. One study reported on the use of a severity measure prospectively. Conclusions: Health records are suitable for assessment of diabetes severity; however, the clinical uptake of existing measures is limited. The need to advance this research area is fundamental as higher levels of diabetes severity are associated with greater risks of adverse outcomes. Diabetes severity assessment could help identify people requiring targeted and intensive therapies and provide a major benchmark for efficient healthcare services. What's new?: Assessing diabetes severity is important and could help identify people in need of targeted therapies and benchmark healthcare services. This is the first systematic review of measures quantifying Type 2 diabetes severity. More severe diabetes was associated with greater risks of hospitalization and mortality. Assessment of diabetes severity using real‐world electronic health records is under‐researched and underutilised in clinical care. None of the studies in the review compared the utility or performance of the developed measures with those of currently‐used indices, mainly HbA1c . Health records are suitable for assessment of diabetes severity. Contemporary, actionable and validated disease‐specific severity measures in large diabetes cohorts are needed.